Characterization of the fatigue behavior of additive friction stir-deposition AA2219. (January 2021) - Anderson-Wedge, K.; Avery, D.Z.; Daniewicz, S.R.; Sowards, J.W.; Allison, P.G.; Jordon, J.B.; Amaro, R.L.
Highlights: The local optimal process parameter set for AFS-D AA2219 is presented. The monotonic tensile response, microhardness, grain size, and precipitate existence are presented. The cyclic plastic response of AFS-D AA2219 is compared to the wrought AA2219 response. Abstract: This work characterizes aluminum alloy (AA) 2219 created by use of the solid-state additive friction stir-deposition (AFS-D) process. Specifically, it determines the "goodness" for use in particular circumstances of as-deposited material created by varied process parameter sets as a function of microhardness and grain size measurements. It presents ideal process parameters for AFS-D AA2219 and characterizes the local optimal as-deposited material by cyclic plastic response, monotonic tensile response, microhardness, grain size, and precipitate existence. Ultimately, this work provides the foundation for the AFS-D technology to be used in construction of NASA's Space Launch System (SLS) vehicle.